Diseño y Construcción de un banco funcional del sistema de encendido transistorizado de un vehículo para la U.A.N (2021)
In this project, the development and construction of a didactic bench was carried out to illustrate to the undergraduate students of the FIMEB faculty of the Antonio Nariño University, the operation of the vehicle ignition system, seeking to integrate theoretical teaching and interaction of the same. For this project, the idea of showing the student the execution of vehicular ignition was raised, to solve the limitations presented by conventional ignition by breaker and capacitor, Limitations such as ignition failures at high revolutions and premature wear of the contacts of the breaker bouncing or sparking To demonstrate the effectiveness of this bank in the learning process, a laboratory guide was developed through which the student will be able to demonstrate the type of response generated by each component; if this coincides with the theory previously given, in addition to serving as a means for the analysis of electrical variables in the vehicle's ignition system.